Linguistic and Statistical Analysis of the Terminology for Constructing the Thesaurus of a Specified Field - M. S. Karyaeva (Моделирование и анализ информационных систем)
The paper is devoted to the analysis of the body of terms and terminological sources for further automation of constructing the thesaurus of a subject area, which is regarded as poetics in our work. Preliminary systematization of terminology with a linguistic and statistical approach forms the body of semantically related concepts to automate extraction of semantic relationships between terms that define the structure of the thesaurus of the specified field.